Effects of precompetition state anxiety interventions on performance time and accuracy among amateur soccer players: Revisiting the matching hypothesis - Abouzekri, O. A.; Karageorghis, C. I. (European Journal of Sport Science, 2010)
In this study, we tested the matching hypothesis, which contends that administration of a cognitive or somatic anxiety intervention should be matched to a participant's dominant anxiety response. Sixty-one male soccer players (mean age 31.6 years, s=6.3) were assigned to one of four groups based on their responses to the Competitive State Anxiety Inventory-2, which was modified to include a directional scale. Interventions were randomly administered in a counterbalanced order 10 min before each performance trial on a soccer skill test. The dominantly cognitive anxious group (n=17), the dominantly somatic anxious group (n=17), and the non-anxious control intervention group (n=14) completed a baseline performance trial. The second and third trials were completed with random administration of brief cognitive and somatic interventions. The non-anxious control group (n=13) completed three trials with no intervention. A mixed-model, GrouptimesTreatment multivariate analysis of variance indicated significant (P<0.05) changes in cognitive anxiety intensity and somatic anxiety intensity, but not in state anxiety direction (P>0.05), or performance time or accuracy (P>0.05). The present findings do not provide support for the matching hypothesis for state anxiety intensity and direction, or for performance.